Effect of thermomechanical loading on fracture resistance and failure mode of new pressable zirconia-reinforced lithium disilicate onlay restoration - Walid A. Abdelhady; Mohamed F. Metwally; Khaled M. Haggag (Tabriz University of Medical Sciences, 2024)
Background. Insufficient information exists regarding the fracture resistance and failure pattern of newly developed zirconia-reinforced lithium disilicate (ZL, Vita Ambria) onlays. This in vitro study compared the fracture resistance of two types of onlays: monolithic lithium disilicate (LD) and monolithic ZL. Methods. Forty-eight ceramic onlay restorations were fabricated on epoxy dies using a maxillary first premolar model. The samples were divided into two main groups: LD and ZL. Half of each group was subjected to thermomechanical fatigue loading (TML) using a chewing simulator. All the samples were cemented with self-adhesive resin cement. Subsequently, they were loaded until failure in a universal testing machine, and the fracture patterns and resistance were recorded. Results. Before TML, ZL demonstrated the highest statistically significant mean fracture resistance (499.76±34.14N) compared to LD (470.40±27.38N). After TML, ZL showed the highest non-statistically significant mean fracture resistance (429.27±131.42N), while LD's mean fracture resistance decreased (377.31±62.18N). Conclusion. Monolithic zirconia-reinforced onlays demonstrated higher fracture resistance and a more favorable failure mode compared to LD. However, the impact of thermomechanical aging resulted in reduced fracture resistance for both materials, with a notable preference observed for ZL.